NILAI DIAGNOSTIK PEMERIKSAAN GRAM, NITRIT, DAN LEUKOSIT ESTERASE URIN PADA INFEKSI SALURAN KEMIH ANAK DI RSUP DR SARDJITO - , HENRY SUTAPA PURBANUGRAHA, dr. Pungky Ardani, SpA(K) ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: Urinary tract infection (UTI) is a prevalent in children and prompt diagnosis followed with adequate therapy will prevent long term complications such as renal failure. Standard for diagnosing UTI is urine culture, however, it is time consuming (3â5 days), relatively expensive, and may be unavariable in some health facilities. Gram staining, nitrite and leukocyte esterase of urine are considered to be potential alternatif method to diagnose UTI. Objective: This study was aimed to determine the diagnostic value of Gram staining, nitrate and urine leukocyte esterase to diagnose UTI, composed the gold standart of urine culture. Method: This study is a diagnostic test with a cross-sectional design and was performed in Dr Sardjito hospital, Yogyakarta. Urine samples were taken from child with UTI suspicious (3-18 years old) by consecutive sampling, and who fulfilled the inclusion and exclusion criteria. It examined by Gram staining under microscopic examination, urinary nitrate and leukocyte esterase by dipstick test, and urinary culture as the gold standard. Result: About 140 children who fulfilled the inclusion and exclusion criteria were included in the study. Triple parallel test (Gram stain, nitrite and leukocyte esterase urine) was found that the sensitivity was 91,0% (95% CI: 84,0-98,0), specificity 92% (95% CI: 81,0-100), positive predictive value 97% (95% CI:92,0-100) and negative predictive value 79% (95% CI:63,0- 94,0), and positive likelihood ratio 10,9 (95% CI: 2,9-41,3). Conclusion: Combination of Gram staining, nitrite and leukocyte esterase in the urine had high sensitivity and specificity to diagnose UTI.